Higher order oscillations of (3+1)D light bullets in linearly inhomogeneous cubic-quintic media - Jasinski, Jerzy (Photonics Letters of Poland, 2012)
In the paper the propagation of (3+1)D axially-symmetric spatio-temporal pulses through cubic-quintic nonlinear Kerr-like with linear graded-index modulation is considered. Analysis of propagation is performed by means of variational method. The approximate solutions of Euler-Lagrange (EL) equations are obtained using multiple scale approximation up to second-order correction terms. The results are compared with numeric solution of nonlinear Schrödinger equation. Full Text: PDF References G.P. Agrawal, "Nonlinear Fiber Optics", (Academic Press, San Diego 2001) J. Jasinski, "Evolution of light bullets propagating in saturable Kerr-like media with higher order effect", Opto-Electron. Rev., 13, 129, (2005) J. Jasiński, M. Kościesza, "Spatio-temporal pulses of the Laguerre-Sech shape in a gradedindex cubic-quintic medium", [CrossRef] S. Raghavan, G. P. Agraval, "Spatiotemporal solitons in inhomogeneous nonlinear media", Opt. Commun., 180, 377, (2000)[CrossRef] V. Skarka, V. I. Berezhiani, R. Miklaszewski, "Spatiotemporal soliton propagation in saturating nonlinear optical media", Phys. Rev. E., 56, 1080, (1997)[CrossRef] D. E. Edmundson, R. H. Enns, "Particlelike nature of colliding three-dimensional optical solitons", Phys. Rev. A, 51, 2491, (1995)[CrossRef] D. Mihalache, D. Mazilu, L.-C. Crasovan, B. A. Malomed. F. Lederer, "Three-dimensional spinning solitons in the cubic-quintic nonlinear medium", Phys. Rev. E, 61, 7142, (2000)[CrossRef] R. F. Abdullatif, R. L Dewar, "Derivation of the Nonlinear Schrödinger Equation by The Derivative Perturbation Expansion Method", Int. J. of Basic and Appl. Sci., 11, 120-124, 2011 A. Biswas, S. Konar, Introduction to non-Kerr Law Optical Solitons, (Chapman&Hall, Boca Raton 2007)